Waste size and lay up sequence strategy for reusing/recycling carbon fiber fabric in laminate composite: Mechanical property analysis - Shiino, Marcos Yutaka [UNESP]; Cipó, Thais Carolina Gonçalves [UNESP]; Donadon, Maurício Vicente; Essiptchouk, Alexei [UNESP] (SAGE Publications, 2021)
Carbon fiber fabrics have been largely used in composite structures as they provide high mechanical strength and potential weigh reduction, allowing more efficiency in product design. However, the production of the parts generates scraps that is discarded as a waste, becoming a challenge to recycle the carbon fiber with predictable mechanical strength. Within this context, this research analyzed strategies of laying up carbon woven fabrics based scraps, in order to reach a desirable mechanical properties in bending loading. Three types of laminates were manufactured using varied fabric size and number of discontinuities in the layup combined with polyethylene terephthalate (PET) film as a matrix. The obtained composites were tested under four-point-bending test and an energy-strength based analysis was conducted. This analysis explained a strategic position of fabric scrap to maximize the bending strength: providing a value of 106.33 MPa for a composite with high number of discontinuities against 83.11 MPa for another with less discontinuity.
Keywords: Flexural test; fracture; reuse; strength of materials; thermoplastic composites